Status and Future Evolution of the ATLAS Offline Software. Issue 7 (December 2015) - Seuster, R; Elsing, M; Stewart, G A; Tsulaia, V
Abstract: These proceedings give a summary of the many software upgrade projects undertaken to prepare ATLAS for the challenges of Run-2 of the LHC. Those projects include a significant reduction of the CPU time required for reconstruction of real data with high average pile-up event rates compared to 2012. This is required to meet the challenges of the expected increase in pileup and the higher data taking rate of up to 1 kHz. By far the most ambitious project is the implementation of a completely new analysis model, based on a new ROOT readable reconstruction format, xAOD. The new model also includes a reduction framework based on a train model to centrally produce skimmed data samples and an analysis framework. These proceedings close with a brief overview of future software projects and plans that will lead up to the coming Long Shutdown 2 as the next major ATLAS software upgrade phase.